Pengaruh Penilaian Kinerja dan Imbalan Terhadap Kepuasan Kerja (Studi pada Karyawan PT. Bimaruna Jaya Jakarta Timur) - Elian, Rama Virgil (SM Institute, 2025)
Thin global competition, companies must be able to read the opportunities that will occur in the future. Therefore, companies need innovative human resources (HR). Companies that have talented and good quality human resources are supported by good employee performance. Performance appraisal is one of the most significant things in the whole series of processes related to human resource activities. Rewards are also called retribution (can be in the form of flattery, punishment and so on) for actions that someone does. One of the strategies that companies must apply to grow and encourage job satisfaction in order to implement better employee performance is to provide rewards commensurate with the employee's hard work. This study aims to determine and describe the Performance Appraisal, Rewards, Job Satisfaction, and to find out and explain the effect of Performance Appraisal and Rewards on Job Satisfaction simultaneously or partially. The type of research used is explanatory research with a quantitative approach. The population used in this study were employees of PT. Bimaruna Jaya, East Jakarta. The sampling technique used is Proportionate Random Sampling with a sample of 67 samples. This study uses statistical data analysis and multiple linear regression analysis. The results of this study indicate that performance appraisal has an effect and significant on job satisfaction. Rewards have an effect and significant on job satisfaction. Simultaneously Performance Assessment and Rewards have an effect and significant on Job Satisfaction. Keywords : Performance Appraisal; Rewards; Job Satisfaction.